Exploring the gastric cancer care pathway in South Africa - Anishka Ramadhar; Juliana Kagura; Mazvita Muchengeti; Cameron Gaskill; Natasha Khamisa (African Journal of Primary Health Care & Family Medicine)
Background: Gastric cancer (GC) diagnosis and care data in South Africa (SA) is sparse, and SA has a high GC mortality rate. Mapping the GC care pathway is needed to explore its efficacy in association with the SA GC burden and mortality.